Interfacial Assembly of Graphene Oxide: From Super Elastic Interfaces to Liquid‐in‐Liquid Printing. Issue 6 (15th December 2021) - Kamkar, Milad; Erfanian, Elnaz; Bazazi, Parisa; Ghaffarkhah, Ahmadreza; Sharif, Farbod; Xie, Ganhua; Kannan, Aadithya; Arjmand, Mohammad; Hejazi, S. Hossein; Russell, Thomas P.; Fuller, Gerald G.; Sundararaj, Uttandaraman
Abstract: Tailoring the oil/water (O/W) interface is a prerequisite for structuring these two immiscible liquids into prescribed architectures, i.e., liquid‐in‐liquid printing, which is an emerging area in material science. Here, assemblies of graphene oxide (GO) at O/W and air/W interfaces are characterized using a wide range of interfacial rheological techniques. It is shown that the GO nanosheets assemble at the interface, even at extremely low concentrations as low as 0.04 vol%, significantly increasing the elasticity at O/W or air/W interfaces. This is attributed to the combined hydrophobic and hydrophilic nature of GO. Interfacial elastic modulus of ≈1800 mN m −1 is achieved, making GO assemblies exceptional candidates for applications where stabilization of the O/W interface is indispensable. Herein, the super elastic character of the O/W interface with GO assemblies is capitalized for all‐liquid 2D printing in a low viscous oil, underscoring the utility of these all‐liquid systems for electronics, fluidic devices, and controlled release systems. Abstract : Super elasticity with the highest ever reported interfacial storage modulus at oil/water interface is achieved in the presence of only 0.04 vol% of graphene oxide, enabling to sculpt water in oil. The work uncovers a new class of materials and opens a new pathway to design all‐liquid systems for electronics, fluidic devices, and controlled release systems.